Involvement of Photosynthetic Carbon Reduction Cycle Intermediates in CO(2) Fixation and O(2) Evolution by Isolated Chloroplasts - Schacter, Bernice (1971)
The photosynthetic carbon reduction cycle intermediates can be divided into three classes according to their effects on the rate of photosynthetic CO(2) evolution by whole spinach (Spinacia oleracea) chloroplasts and on their ability to affect reversal of certain inhibitors (nigericin, arsenate, arsenite, iodoacetate, antimycin A) of photosynthesis: class I (maximal): fructose 1, 6-diphosphate, dihydroxyacetone phosphate, glyceraldehyde-3-phosphate, ribose-5-phosphate; class 2 (slight): glucose 6-phosphate, fructose 6-phosphate, ribulose-1, 5-diphosphate; class 3 (variable): glycerate 3-phosphate. While class 1 compounds influence the photosynthetic rate, they do not lower the Michaelis constant of the chloroplast for bicarbonate or affect strongly other photosynthetic properties such as the isotopic distribution pattern. It was concluded that the class 1 compounds influence the chloroplast by not only supplying components to the carbon cycle but also by activating or stabilizing a structural component of the chloroplast.